The Influence of Strategic Agility, Dynamic Capabilities, and Business Model Innovation on Sustainable Business Performance of MSMEs Managed by Generation Z - Ade Suhara; Ratna Tri Hari Safariningsih; Mirza Syahviyar; Titis Nistia Sari; Anita Bawaiqki Wandanaya; Amat Suroso (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study at hand intends to measure the contribution of strategic agility, dynamic capabilities, and business model innovation, as the main factors, to the sustainable performance of the Millennials or Gen Z led Micro, Small and Medium Enterprises (MSMEs). The research is inspired by the digital economy where small and medium enterprises play an increasingly crucial role, and the youth entrepreneurs need to make their businesses survive in the tough and ever-changing market. The study is conducted using a quantitative explanatory method on a sample of 150 Generation Z MSMEs. Purposive sampling of factors like the time in business, the use of digital technology, and participation in business innovation was the sampling technique used. The questionnaire which was the research instrument underwent validation through item and total score correlation t-test and its reliability was determined by Cronbach's Alpha. Normality, heteroscedasticity, and multicollinearity were tested prior to regression analysis. Multiple linear regression analysis showed that all three independent variables had a positive and significant influence on business performance sustainability. The results of this study provide a substantial contribution to the strategic management of the young generation MSMEs literature. One of the research results is the practical application of the findings for Generation Z MSMEs in terms of their agility strategies, capability development, and business model innovation to ensure their long-term sustainability advice.